Analisis Strategi Pengembangan Wahana Tirta Pesona di Kota Bandar Lampung - Jumini Rahayu; Aprilianto Amir; Hinfa Mosshananza (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2023)
Tourism is an activity carried out by individual or group in the form of a trip to visit a certain place with the aim of having a vacation, and seeing the features and beauty of this tour. Tirta Pesona rides are one of the tours located in the city of Bandar Lampung. The purpose of this study was to analyze the strategy for developing Wahana Tirta Pesona tourism in the city of Bandar Lampung. The type of research used in this study is a type of qualitative research. Based on the results of interviews, the main attraction of the Wahana Tirta Pesona tourist attraction is the natural beauty that is very natural. So that the management goes according to the planned objectives in the tourism development strategy where the manager focuses on developing facilities and increasing promotions so that the number of visitors does not continue to decrease. The techniques and planning possessed by the Wahana Tirta Pesona tourist attraction are quite good, but are not running effectively in their implementation. Based on the results of interviews and observations, it can be concluded that the development strategies at tourist sites that have been carried out have been implemented but are still ineffective, resulting in a decrease in the number of visitors. The decrease in the number of visitors was caused by several other factors such as the impact of the Covid'19 pandemic, lack of promotional activities, lack of maintenance, and lack of access road facilities and infrastructure to the location. The management has tried to develop tourism objects including constructing other supporting facilities. Keywords: development strategy, strategy implementation, tourism